STRATEGI PENERIMAAN PAJAK KENDARAAN BERMOTOR DI KOTA PEKANBARU - Deangella Novyra; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The motor vehicle tax revenue strategy is a new breakthrough made by the Regional Revenue Agency of Riau Province which aims to increase motor vehicle tax revenue, especially in Pekanbaru City. With the presence of the strategy created, it is hoped that it will make it easier for the public to pay motor vehicle taxes and the public has a high awareness of paying motor vehicle taxes on time. The purpose of this study is to determine how the implementation of the strategy that has been implemented and to find out what are the supporting and inhibiting factors of the implementation of motor vehicle tax revenue strategies in Pekanbaru City. This study used interactive analysis techniques with qualitative research types using descriptive approaches and data both primary and secondary data obtained through observation, interviews, and documentation are then analyzed based on research problems. The results of this study indicate that the strategy for motor vehicle tax revenue in Pekanbaru City in motor vehicle tax revenue has not been fully implemented. The supporting factors for the motor vehicle tax revenue strategy are human resources and facilities and infrastructure. Inhibiting factors are the lack of socialization and the lack of public awareness of taxpayers in paying motorized vehicle taxes in Pekanbaru City. Keywords: strategy, acceptance, motor vehicle tax